Ancaman dan Tantangan Muslim Indonesia Di Era Perang Proksi - Affan, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2018)
Proxy war is the intervention of a third party in one of the factions to fight another faction. The Arab Spring and the Syrian Civil War as well as the lone wolf attack IS (Islamic State) are one of its manifestations. In the future, proxy war will be a method commonly used in conflict. This is because the progress of information and communication technology has facilitated the implementation of proxy war. The progress of information and communication technology also made this era an era of proxy war. The following study aims to outline the threats and challenges facing Indonesian Muslims in the era of proxy war. The results of the study are expected to broaden the perspective of Islamic studies by raising the subject of studies that have not yet been studied but are also expected to have positive implications in proxy war discourse. The method used in the study is literature review. The results of the study indicate that proxy-forming narratives are a threat as well as the main challenges faced by Indonesian Muslims in the era of proxy war. To deal with it, Indonesian Muslims are required to have deeper religious knowledge and broad religious insights.